Demystifying social finance and social investment - Salway, Mark; Palmer, Paul, 1955-; Grant, Peter, 1955 February 21- (New York : Routledge, 2020)
"Social Finance and Social investment are not challenging concepts to grasp. They use commercial-style investment tools to create a social as well as a financial return. The application, however, is not always as straightforward. This book begins in the wider field of social finance but focuses primarily on social investment as a tool. The reader is helped to understand this from different angles: introducing social investment, discussing social investment and taking a 'deep-dive' into it to bring it to life. This unique book takes the reader on a journey from first principles to detailed practical application. This book examines the policy context and asks why social investment has only recently become so popular, when in reality this is a very old concept. This is linked to the agenda of making charities more 'business-like', set against the changing face of investment, as charities can no longer rely on donations and grants as guaranteed income. The work they do is more important than ever and social investment, used with care, offers a new opportunity that is further explored in this text. Mark Salway, Paul Palmer, Peter Grant and Jim Clifford will help readers understand how a small amount of borrowing, or a different business model focused away from grants and donations, could be transformational for the non-profit sector"--
OCLC-licensed vendor bibliographic record.
Keywords: Charities -- Finance; Charities -- Accounting; BUSINESS & ECONOMICS / General